Recurrent dislocation of the temporomandibular joint: a literature review and two case reports treated with eminectomy. Issue 2 (April 2014) - Martins, Wilson Denis; Ribas, Marina de Oliveira; Bisinelli, Julio; França, Beatriz Helena S.; Martins, Guilherme
<x content-type="archive" xml:space="preserve">Abstract</x> Aims: Dislocation of the temporomandibular joint (TMJ) is a troublesome condition that occurs in a chronic or acute form. It is a distressing and highly embarrassing situation that may occur as a result of daily activities such as yawning, laughing, or during events that require keeping the mouth open for a long time. This review aims to present and discuss different conservative and surgical techniques to treat patients with a dislocated mandible, and to present two cases of surgical treatment. Methodology: A search of the literature was completed (Medline, PubMed) using the keywords TMJ dislocation, TMJ luxation, mandibular dislocation and surgical and non-surgical methods of treatment for this condition. Results: Eminectomy (Myrhaug's surgery) has been used with satisfactory results. Most of reports present large series of patients with more than one year of follow-up and no recurrence of complications. Is less invasive and take a short operation time; need no bone transplantation or placing any kind of foreign body into the joint. Conclusion: Eminectomy results in long-term resolution of recurrent TMJ dislocations, when compared with others surgical techniques.